KERJASAMA LEMBAGA PEMBERDAYAAN MASYARAKAT (LPM) KUTA DENGAN KEPOLISIAN DALAM MENANGGULANGI TINDAK PIDANA PENCURIAN - Ni Komang Ratih Kumala Dewi (University of Udayana, 2015)
The rampant of crime of theft by pickpocket mode in the Kuta area has given a negative impacton tourism. In Kuta area, there are an institution is engaged in community empowermentwhich is called Lembaga Pemberdayaan Masyarakat (LPM). LPM has a mission which isparticipate to increase law awareness and encourage law enforcement, through this missionwas related a cooperation from police Department and LPM. Therefore, it is importantthat is studied in depth about the cooperation of LPM and Police Department in mitigatingthe crime of theft by pickpocket mode in Kuta area and also its constraints and preventioneffort. The method of research which used is the empirical law research by the qualitativedescriptive method. The data consists of primary data and secondary data. The technique ofcollecting data which is used the document study and interview technique. The technique ofdetermine the sample used non probably sampling. The result found that the LPM role is toassist the police officer if it found a crime in area when the jagabaya and hansip (securityofficer) do their job. Related to the constraints which is faced by LPM and police officerthat LPM does not has infrastructure, technical, and administrative. It is also does not hasa legal protection to do investigation. Those constraints is tried to fulfill by the police officerand LPM however the legal protection of LPM is still does not found a solution. The role ofLPM is still assist to catch and prosecute the executants in a while.